Implementasi Konsep Fungsi Dalam Perancangan Basis Data Sederhana Pada Sistem Informasi Akademik - Naura Hazirah; Musanna; Putri Nur Assyifa; Yusnidar; Maryana (JIKUM: Jurnal Ilmu Komputer, 2026)
Academic data management that is not designed with a good database structure often results in data duplication, inconsistency, and difficulties in system maintenance. This study aims to apply the concept of functions, specifically functional dependencies, in designing a simple database for an academic information system that includes data on students, lecturers, courses, study plan cards (KRS), and grades. The research method used is descriptive, with the stages of needs analysis, Entity Relationship Diagram (ERD) design, functional dependency analysis between attributes, normalization to third normal form (3NF), and implementation and testing in MySQL. The results show that the application of the function concept successfully identified six main functional dependencies that form the basis for the formation of five normalized tables: Students, Lecturers, Courses, KRS, and Grades. Query testing on the resulting database showed no data redundancy and all insertion, update, and deletion anomalies were avoided. This study concludes that the function concept is an important foundation in designing an efficient and consistent relational database in small to medium-scale academic information systems.